2016
DOI: 10.1111/jocn.13375
|View full text |Cite
|
Sign up to set email alerts
|

Day surgery nurses' selection of patient preoperative information

Abstract: Aims and objectives. To determine selection and delivery of preoperative verbal information deemed important by nurses to relay to patients immediately prior to day surgery. Background. Elective day-case surgery is expanding, patient turnover is high and nurse-patient contact limited. In the brief time-frame available, nurses must select and precisely deliver information to patients, provide answers to questions and gain compliance to ensure a sustained, co-ordinated patient throughput. Concise information sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 59 publications
0
14
0
2
Order By: Relevance
“…Besides the incentives to increase efficiency and reduce costs associated with expensive hospital stays, day surgery has been shown to prevent postoperative complications as a result of hospitalization, and this form of treatment is often the patients' own preference. 1,2 Day surgery is found to enhance patient satisfaction and have less impacts on their families' daily life and routines. 3 Patients undergoing day surgery are normally discharged from the hospital on the same day after the operation.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the incentives to increase efficiency and reduce costs associated with expensive hospital stays, day surgery has been shown to prevent postoperative complications as a result of hospitalization, and this form of treatment is often the patients' own preference. 1,2 Day surgery is found to enhance patient satisfaction and have less impacts on their families' daily life and routines. 3 Patients undergoing day surgery are normally discharged from the hospital on the same day after the operation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has reported that the relatively short time from the admission to undergo outpatient surgery to their discharge is a factor that restricts the assessment of patients by nurses in the pre-surgery period, the information of patients and their families before the operation, their monitoring in the postsurgery period and providing them care in line with their needs and monitoring the problems arising in the post-surgery period. 1,5,18,19 It is thought that such a situation comes into the picture due to nurses' negligence to meet their responsibilities with respect to training, a negligence probably arising from the increased workload. There is also a shortage of nurses and nurses' workload is high in the hospital where the research was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,10 If, however, the process is not effectively planned, outpatient surgery can cause several problems, as a result of which patients can experience some difficulties. 5,7,10,11 Of the various problems that might arise in outpatient surgery, the most prominent are the need for sufficient number of personnel with experience, the short span of time nurses allocate to patients in the post-surgery period, the need for an efficient training for the period after discharge, but, on the other hand, insufficient time available for such a training, lack of insufficient time for the assessment of complications that might come into the picture in the post-surgery period, making it impossible to monitor the complications after the discharge and the need for a caregiver in the first 24-48 hours. 2,3,12 Patients can have difficulty in coping with the problems they experience at home after their discharge.…”
mentioning
confidence: 99%
“…The first part asks for general information of the patients and medical staff. The second part is a preoperative teaching questionnaire (PTQ) 9. Participants were asked to rate accurately what day surgery information they perceived as important on a five-point Likert-type scale that includes ratings from 5 (very important) to 1 (not important).…”
Section: Methodsmentioning
confidence: 99%